On the Analysis of Accuracy for the Estimation of CO2 Emission by Utilizing International I-O Table - SUN De-Hua; ITO Kazuho; SUZUKI Yoshihiko (環境科学会誌, 1999)
The aim of this paper is to analyze the accuracy of estimation value of CO2 emission derived from the I-O analysis. The paper utilizes the international I-O table for the consideration. In the estimation of the value of CO2emission, two methods are utilized in the analysis up to now. This paper considers the accuracy of 4 estimation methods, which are 2 known methods and new 2 methods. The paper shows the accuracy with the root square error between the standard value and the estimated value. From the analysis, this paper shows that the estimated value derived from (I-A)-1? F estimation method is the best in general. 地球温暖化問題の深刻化とCOP3における温室効果ガス削減という課題に直面する現在,私たちの消費行動がCO2排出にどのように関わっているのかを正確に知ることは最重要課題の一つといえる。消費行動に伴うCO2排出量の産業連関表を用いた推定方法としては,2つの方式が知られている。本文ではこれら2つの方式を含め,産業連関表を利用した推定方式の推定精度について考察している。